2019
DOI: 10.12688/f1000research.18274.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of zirconia-reinforced lithium silicate partial coverage crowns compared to lithium disilicate partial coverage crowns. A randomized controlled split-mouth clinical study

Abstract: Background: Despite the fact that preliminary clinical results of conservative partial coverage restorations (PCRs) are promising, the clinical behavior of different PCR ceramic materials is rarely investigated in clinical trials. This study aimed to evaluate the clinical outcomes of partial coverage restorations (PCR) fabricated with zirconia-reinforced lithium silicate ceramic system compared to partial coverage restorations fabricated with lithium disilicate ceramic system. Methods: 46 vital premolars and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 38 publications
1
18
0
6
Order By: Relevance
“…Thirty-five of the included articles were excluded with reasons given for their exclusion shown in Figure 1 . The nine remaining studies were included in qualitative and quantitative data synthesis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. During an updated search on 1 February 2021, only one additional clinical study was found, but was not included as it was a case series.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-five of the included articles were excluded with reasons given for their exclusion shown in Figure 1 . The nine remaining studies were included in qualitative and quantitative data synthesis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. During an updated search on 1 February 2021, only one additional clinical study was found, but was not included as it was a case series.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nine included studies, five investigated PICN [ 37 , 38 , 40 , 43 , 44 ] and four investigated ZLS ( Table 2 ) [ 39 , 41 , 42 , 45 ]. Studies investigating PICN were published from 2016 to 2020 and had follow up periods ranging from 2 to 3 years, of which four had a prospective study design [ 38 , 40 , 43 , 44 ] and one retrospective design [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations